Singwǣtlō̜m mư̄ang læ chumchon yangyư̄n (Samnakngān Nayōbāi læ Phǣn Sapphayākō̜n Thammachāt læ Singwǣtlō̜m, Krasūang Sapphayākō̜n Thammachāt læ Singwǣtlō̜m, 2011)
On management and development of natural resources and environment for sustainable communities in Thailand.